Geology of the Curone and Staffora Valleys (NW Italy): field constraints for the Late Cretaceous – Pliocene tectono-stratigraphic evolution of Northern Apennines - Edoardo Barbero; Andrea Festa; Gianfranco Fioraso; Rita Catanzariti (Journal of Maps, 2017)
In the northwestern part of Northern Apennines, between Curone and Staffora Valleys, the tectonic superposition between the External Ligurian Units (i.e. the ophiolitic-bearing chaotic complex of the Groppallo Unit and the non-ophiolitic Cassio Unit), the Middle Eocene – Miocene wedge-top basin Epiligurian Units succession, and the Late Messinian – Pliocene Po Plain succession, records the multistage tectono-stratigraphic evolution from subduction to continental collision. Our geological map, at the 1:20,000 scale, allows us to define 6 main tectonic stages on the basis of (i) the crosscutting relationships between main faults and local to regional stratigraphic unconformities and (ii) the differentiation among different types of chaotic rock unit (olistostromes and broken formations) deposited since Late Cretaceous to late Messinian. This approach provides a new understanding on the tectono-stratigraphic evolution of this sector, and its meaning in the evolution of the northwestern part of Northern Apennines.